2015
DOI: 10.1186/s12909-015-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring teams of learners becoming “WE” in the Intensive Care Unit – a focused ethnographic study

Abstract: BackgroundResearch about collaboration within teams of learners in intensive care is sparse, as is research on how the learners in a group develop into a team. The aim of this study was to explore the collaboration in teams of learners during a rotation in an interprofessional education unit in intensive care from a sociocultural learning perspective.MethodsFocused Ethnographic methods were used to collect data following eight teams of learners in 2009 and 2010. Each team consisted of one resident, one special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Furthermore, resonating with Conte et al [ 19 ] we also suggest that socio-cultural frameworks can provide useful insights not just into the situated and relational nature of learning, within real-world interprofessional settings, but also into how students may construct and negotiate their professional identity. Understanding how students traverse professional boundaries and identities has emerged from preliminary work exploring health professional education in longitudinal integrated clinical placements where up to 30 students from different professions were placed at any one time in a rural community [ 24 ].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, resonating with Conte et al [ 19 ] we also suggest that socio-cultural frameworks can provide useful insights not just into the situated and relational nature of learning, within real-world interprofessional settings, but also into how students may construct and negotiate their professional identity. Understanding how students traverse professional boundaries and identities has emerged from preliminary work exploring health professional education in longitudinal integrated clinical placements where up to 30 students from different professions were placed at any one time in a rural community [ 24 ].…”
Section: Introductionsupporting
confidence: 81%
“…These include the recently published study by Conte et al . [ 19 ], which used socio-cultural learning theory as a lens to explore team collaboration during an interprofessional education rotation in intensive care. This study showed the importance of situated learning and guided participation within the clinical setting, and in particular the links between learner ownership and legitimate peripheral participation.…”
Section: Introductionmentioning
confidence: 99%
“…Reflectivity, both on an individual level and within the team has been discussed as prerequisites for successful team collaboration (Conte et al 2015a ). Team collaboration is an important part of professionals’ engagement in practice and improves health outcomes (Conte et al 2015a , b ; World Health Organization 2010 ). The benefits of formal peer-support, for example mentorship, have been acknowledged in prior studies to support a new professional’s development and strengthen the sense of team unity (Chen and Lou 2014 ; Kalen et al 2012 ; Rush et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another challenging aspect involved in the transition into a new professional identity is finding one’s own part to play in the new professional practice and becoming a legitimate member of the team (Bridges 2009 ; Conte et al 2015b ). Becoming a legitimate member of a team is essential for successful team work, patient safety and retention (Numminen et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Junior year students usually require more support and guidance than senior students so extent of interprofessional involvement needs to be carefully matched with student capability to minimize risk to patients and/ or themselves. Supervisors have an important role to play in guiding students as they move from peripheral 'observers' to more engaged and legitimate contributors to collaborative patient care (Conte et al 2015). Identifying a specific work setting or activity where students can meet requisite interprofessional learning outcomes is important and university staff should check with the leaders and educators at placement sites that experiences that assist students reach their goals will be available during the placement (Henderson et al 2007).…”
Section: Scaffold Interprofessional Learning Opportunities To Studentmentioning
confidence: 99%